METHODS OF CORRECTING MISTAKES IN WRITTEN SPEECH - S. A. Chekanova (Vestnik MGIMO-Universiteta)
Mistake correction is an important element of teaching a foreign language. It is important to do it in the right way and in a proper time so that students can remember a grammatically correct variant. Here it is necessary to pay attention to a psychological aspect. Some students negatively react to a great number of the teacher’s corrections in their notebooks. In this case it is possible to classify mistakes into grave and minor ones. Besides the teacher should first mention his students’ progress in a particular unit and then the material they ought to revise. Mistakes must be generalized, commented on and analyzed. It is essential not only for improving students’ linguistic knowledge but also for the teacher who can use the data to explain the same material to other students. The teacher will call their attention to certain points so that they can avoid typical mistakes. The article is devoted to various ways of correcting grammar mistakes in writing. The aim of the article is to choose methods that will enable students to improve their writing skills. It briefly describes each of the methods and explains why it may be reasonable to apply it to teaching and why it may be useful for students with different language experience.